Geomorphological features and processes in the Sierra de Famatina, La Rioja - Fucks, Enrique Eduardo (2018)
The Sierra de Famatina is considered the highest elevation outside the Argentine Andes Cordillera, being the General Belgrano hill, 6097 masl, the main height. This altitudinal situation favored the development of glaciers during the cold events of the cyclical Quaternary climatic fluctuations, giving shape to a territory with very complex morphologies. The aim of this contribution is to describe the current and past geomorphological processes in the vicinity of the highest sector of the Sierra de Famatina through different forms of the landscape, which put together allow the recognition of the geomorphological evolution of the region. At present, extreme weather lead to periglacial conditions above 4000 m and glacial above 6000 m, generating ice and snow patches almost without movements in flat to flat-concave sections of the watersheds, and rock glaciers, gelifluction lobes and earth hummocks in cirques, troughs and walls of valleys. Depending on the features of glacial accumulation, three cold events can be recognized, the youngest one (MIS2) with limited distribution, is restricted to the heads of troughs and cirques, from whose deposits the rock glaciers develop. The second one, observed near Puesto Tres Piedras, is represented by moraine-shaped glacier deposits above 3000 m height, and would belong to the Middle-Late Pleistocene. The oldest glacier deposits, early-middle Pleistocene, are in higher topographies. Below 3000 m, valleys are rocky and steep-sided, with permanent courses due not only to low rainfall, but mainly to the melting of the permafrost, forming important reservoirs of water.